The aesthetic perception of orthodontic specialists, general dentists and laypeople regarding different smile displays for a patient missing one upper lateral incisor and the other one peg-shaped - Montinaro, Federica; Nucci, Ludovica; Chiarenza, Maria Chiara; d’Apuzzo, Fabrizia; Perillo, Letizia; Grassia, Vincenzo (Frontiers in Dental Medicine, 2025)
BackgroundThe prevalence of maxillary lateral incisor agenesis ranges from 1% to 3%, with slight global variability. The unilateral agenesis of the maxillary lateral incisor is often associated with a contralateral tooth with microdontia or a peg shape and can have esthetic, functional, and psychosocial implications for patients. The aim of the present survey was to assess the perceptions of smile aesthetics among orthodontists, general dentists and laypeople on different treatment choices, modifying the initial condition of the right maxillary lateral incisor agenesis and the contralateral peg-shaped tooth.MethodsA series of 6 photographs of different smile simulations were presented to 109 orthodontic specialists, 109 general dentists and 141 laypeople through an online survey. Each photograph was duplicated and judged from 1 to 10 for 2 different bipolar adjectives.ResultsStatistically significant results were found for all the groups investigated. All three groups preferred the photo that maintained the typical symmetrical ‘high-low-high gingival contour. Moreover, both orthodontic specialists and general dentists preferred unilateral mesialization of the canine and conservative rehabilitation of the peg-shaped incisor. In contrast, the laypeople preferred bilateral mesialization of the canines with peg-shaped incisor avulsion.ConclusionThe normal symmetrical array of the central incisor, lateral incisor and canine had the best aesthetic results for all subjects. Laypeople were more attracted to a symmetrical smile than were the groups of orthodontic specialists and general dentists.